Formulation Development and Bioavailability Assessment of Aripiprazole by Self-Nanoemulsifying Drug Delivery Systems (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The aim of the present study was to develop a self-nanoemulsifying drug delivery system (SNEDDS) for the oral delivery of aripiprazole (APZ), an antipsychotic drug used in the treatment of schizophrenia. Objectives: In this investigation, attempts were made to enhance the aqueous solubility of APZ through SNEDDS and to assess its effect on oral bioavailability (BA) in rabbit. Materials and Methods: Self-emulsifying drug delivery systems of APZ were formulated with Anise essential oil as oil phase, Gelucire 44/14 as surfactant, and Transcutol HP as cosurfactant after screening various vehicles. Drug-excipient interactions were studied by Fourier transform infrared analysis. The formulations were evaluated for self-emulsifying ability, clarity, and stability of their aqueous dispersion after 48 h, and phase diagram was constructed to optimize the system. Selected formulations were characterized in terms of droplet size distribution, zeta potential, and cloud point and subjected to in vitro drug release studies. The BA of optimized formulation was assessed in Rabbits. Results and Discussion: The formulation was optimized by considering smaller droplet size, higher zeta potential, and faster rate of drug release and found to be robust to different pH media and dilution volumes and remained stable after three freeze-thaw cycles and stored at 4Â°C and 25Â°C for at least 3 months without showing significant change in droplet size. The pharmacokinetic study in rabbits showed that SNEDDS has significantly increased the area under the curve. Conclusion: SNEDDS can be effective oral dosage form for enhancing aqueous solubility and thereby improving oral BA of poorly water-soluble drug, APZ.